2014 IEEE International Parallel &Amp; Distributed Processing Symposium Workshops 2014
DOI: 10.1109/ipdpsw.2014.90
|View full text |Cite
|
Sign up to set email alerts
|

Application Power Signature Analysis

Abstract: The high-performance computing (HPC) community has been greatly concerned about energy efficiency. To address this concern, it is essential to understand and characterize the electrical loads of HPC applications. In this work, we study whether HPC applications can be distinguished by their power-consumption patterns using quantitative measures in an automatic manner. Using a collection of 88 power traces from 4 different systems, we find that basic statistical measures do a surprisingly good job of summarizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Our literature search resulted in only a small amount of closely-related work. In [14], the authors apply clustering techniques on HPC power data to fingerprint applications. The authors rely on six time domain features and demonstrate that such features are enough to differentiate between the ten programs used for testing.…”
Section: High Performance Computingmentioning
confidence: 99%
“…Our literature search resulted in only a small amount of closely-related work. In [14], the authors apply clustering techniques on HPC power data to fingerprint applications. The authors rely on six time domain features and demonstrate that such features are enough to differentiate between the ten programs used for testing.…”
Section: High Performance Computingmentioning
confidence: 99%
“…More recently, Hsu et al developed power signatures based on short statistical summaries of applications' power traces [10]. However, they evaluated them only qualitatively, by visual inspection of the clusterings they yielded for a small dataset, and they did not attempt to compare them to results based on time-series metrics or signatures with more complex features.…”
Section: Related Workmentioning
confidence: 99%
“…We choose these two features as our initial signature, following the work of Hsu et al [10], which showed qualitatively that combining two location parameters seemed to yield good clusterings for power traces.…”
Section: B Feature-vector Representationmentioning
confidence: 99%